The effectiveness of training program in multiskills training centre / Muhammad Zakie Azmin Ismail - Ismail, Muhammad Zakie Azmin (2015)
Training is the process to improve and teaching an individual or an organization (Goldstein & Ford 2002). In order to survive In this competitive and fast change environment, many of organizations regardless of size and type are more emphasizing on the use of Human Resource Capital. Organizations are facing difficulty in terms of acquiring a talented new quality employee, ongoing improvement on the operation, advents of advance technology and retention of workers who are motivated in attain a good life experience. These criteria will likely to influences the success of any organization.